Role of the microbiota in inflammation-related related psychiatric disorders - Zhou, Liying; Wu, Qunhua; Jiang, Lin; Rao, Jiaoyu; Gao, Jianlin; Zhao, Fang; Wang, Xiaokang (Frontiers in Immunology, 2025)
The immune interactions within the gut–brain axis represent a critical etiological factor in psychiatric disorders. The gut microbiota and their metabolites serve as biological mediators that regulate neuroimmune activation and suppression in the central nervous system (CNS). During intestinal immune activation, pro-inflammatory cytokines (e.g., IL-6, TNF-α) propagate to the CNS via compromised blood–brain barrier (BBB) integrity or vagal afferent fibers, disrupting neurotransmitter metabolism and inducing microglial hyperactivation, thereby exacerbating neuroinflammation. Microglia, the principal immune sentinels of the CNS, adopt a pro-inflammatory phenotype upon peripheral inflammatory signaling characterized by morphological transformations, excessive chemokine/cytokine production (e.g., IL-1β, IL-6), and dysregulated neurotransmitter dynamics. These mechanisms are strongly implicated in neuropsychiatric conditions such as major depressive disorder, anxiety disorders, autism spectrum disorder, and schizophrenia. Emerging microbiota-targeted therapies, including probiotic interventions and fecal microbiota transplantation, demonstrate therapeutic potential by restoring tryptophan homeostasis and modulating systemic inflammation. This review synthesizes current evidence on the regulatory role of the gut microbiota in inflammation-related psychiatric disorders, specifically emphasizing the microbial modulation of neuroimmune crosstalk and neurotransmitter synthesis (e.g., serotonin, dopamine). Mechanistic insights into microbial metabolites, such as short-chain fatty acids and tryptophan derivatives, are critically evaluated for their dual roles in psychiatric disorders. These findings advance a unified framework for managing psychiatric comorbidities through precision modulation of the gut–brain axis.